1990
DOI: 10.1148/radiology.175.3.2343128
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth-plate abnormalities: MR imaging of bony-bridge formation in rabbits.

Abstract: The formation of a bony bridge across the growth plate was studied with magnetic resonance (MR) imaging, tomography, and histologic examination in 12 rabbits. Histologic studies performed 0-8 weeks after the creation of a defect in the physis demonstrated transphyseal bone formation with no evidence of cartilage repair. Gadolinium enhancement indicated the development of vascularity through the plate, which preceded the formation of a bony bridge. Enhancement was faint at 4 days after surgery, was inhomogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 0 publications
5
33
0
3
Order By: Relevance
“…Our study indicated that infiltration of mesenchymal cells into the growth plate injury site preceded and/or coincided with the bone bridge formation. Consistently, presence of fibrous mesenchymal cells at the early stage after growth plate injury was also observed in previous studies [13,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study indicated that infiltration of mesenchymal cells into the growth plate injury site preceded and/or coincided with the bone bridge formation. Consistently, presence of fibrous mesenchymal cells at the early stage after growth plate injury was also observed in previous studies [13,15].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our study confirmed the rapid time course of bone bridge formation at the growth plate injury site, and was consistent with previous investigations that used a similar drill-hole injury model in rabbits, rats, and mice. These earlier studies reported either initial or full osseous bar formation at the injury site by 1-3 weeks post-surgery [5,9,13,15,16]. in a Salter type I fracture model of proximal tibia1 physis in young rats, bony bars were found at day 10 after fracture [20].…”
Section: Discussionmentioning
confidence: 97%
“…The fibrogenic phase has been observed on days 3-7 post-injury in injured growth plate of rats, involving an influx of vimentin (mesenchymal cell marker)-immunopositive mesenchymal cells ), a response which is similar to the infiltration of mesenchymal cells following the inflammatory phase at bone fracture sites (Jaramillo et al 1990, Schindeler et al 2008. At the growth plate injury site, some of these cells were found to express growth factors including BMPs (Ngo et al 2006), plateletderived growth factor (PDGF) and FGF2 ) and receptors for BMPs and PDGF (Ngo et al 2006).…”
Section: The Fibrogenic Phasementioning
confidence: 99%
“…The immature bone marrow of the New Zealand white rabbit is a model well suited for the current study since hematopoietic marrow is found within the central skeleton and its MR appearance has been well described before. 32,33 In addition, good anatomical resolution can be achieved for rabbits using a clinical MR scanner, which would not have been possible for smaller rodents. Our findings still have to be confirmed in humans.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%